Family’s Economic Level and Culture Correlate with Nutritional Status of Children Under Five Years - Abdul Muhith; Nursalam Nursalam; Lutfi Ana Wulandari (Universitas Airlangga, 2014)
Introduction: Nutrition is an important thing for human life. Variety in family’s economic level and culture have effect on family’s eating habit. Family with higher economic status have big opportunity to met under fi ve year’s nutrition. Cultural diversity on each family has an impact on the difference of raw food selection, processing methods, and presentation of food. The purpose of this study was to determine the correlation between family’s economic level and culture with nutritional status of children under fi ve year.Methods: Research design was observational analytic with cross sectional approach. The population were mother and their children under fi ve years at Desa Jatigono Kunir, Kabupaten Lumajang. Sampel were 184 respondents, taken by using cluster sampling. Independent variables were family’s economic level and culture. Dependent variable was nutritional status of children under fi ve years. Data were collected by using questionnaire and observational sheet. Then, data were analyzed by using Spearman Rho Test with α<0.05.Results: The results showed that 140 (76.1%) respondents have low economic level, 105 (57.1%) respondents have negative culture in children’s nutrition, and 89 (48%) respondents have good nutritional status. The result of Spearman-rho test showed that family’s economic level (p=0.000) and culture (0.019) have correlated with nutritional status of children under five years.Conclusion: It can be concluded that family’s economic level and culture have correlated with nutritional status of children under fi ve years. Nurses should develop health education and counseling to improve family’s knowledge about nutrition, so children will have good nutritional status.